2014
DOI: 10.1073/pnas.1320649111
|View full text |Cite
|
Sign up to set email alerts
|

Communicating science-based recommendations with memorable and actionable guidelines

Abstract: For many domains of basic and applied science, a key set of scientific facts is well established and there is a need for public action in light of those facts. However, individual citizens do not consistently follow science-based recommendations, even when they accept the veracity of the advice. To address this challenge, science communicators need to develop a guideline that individuals can commit to memory easily and act on straightforwardly at moments of decision. We draw on research from psychology to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…The poor actionability of these materials may be related to the developers because detailing all behaviours into an actionable message is difficult and time consuming, and it is easy to overestimate how easy something is for someone else to do. 52 Second, in the assessment of SAM-C, the graphic category received the lowest score, and all participants emphasised the role of pictures in improving their comprehension and memory of texts. Educational theory suggests that presenting congruent information in multiple formats can help to increase comprehension.…”
Section: Discussionmentioning
confidence: 93%
“…The poor actionability of these materials may be related to the developers because detailing all behaviours into an actionable message is difficult and time consuming, and it is easy to overestimate how easy something is for someone else to do. 52 Second, in the assessment of SAM-C, the graphic category received the lowest score, and all participants emphasised the role of pictures in improving their comprehension and memory of texts. Educational theory suggests that presenting congruent information in multiple formats can help to increase comprehension.…”
Section: Discussionmentioning
confidence: 93%
“…Research suggests that terminology such as ‘nutrient density’ is used only by limited audiences, and so, there is a need for translation into language understood and preferred by consumers in order to engage them in discussions about diet quality (Bucher et al ). Effective communication of nutrient density may perhaps best be undertaken with the support of behaviour change and communications experts, with a focus on the actionability and memorability of messages, activating people’s behaviour using recognised techniques (such as ease of visualisation, chunking and sequencing information into manageable units, specifying when to act and embedding triggers) (Ratner & Riis ). For example, communication to consumers should consider the fact that information retention is greater after seeing audio/visual materials ( e.g .…”
Section: Communication and Behaviour Changementioning
confidence: 99%
“…Their central assumption was that high-risk perception would promote preparation. However, recent review literature showed that the relationship between risk perception and behavior was weak or even null (Bubeck, Botzen, & Aerts, 2012;Ratner & Riis, 2014;Shreve et al, 2014;Solberg et al, 2010;Wachinger, Renn, Begg, & Kuhlicke, 2013).…”
Section: Social Norm Approaches On Disaster Risk Reductionmentioning
confidence: 99%